The reformation of the decalogue : religious identity and the ten commandments in England, c.1485-1625 - Willis, Jonathan P. (Cambridge studies in early modern British history., 2017)
Explores how the English Reformation transformed the meaning of the Ten Commandments, which in turn helped shape the Reformation itself.